1980
DOI: 10.1056/nejm198012253032602
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Sulfasalazine and Its Metabolites in Patients with Ulcerative Colitis and Crohn's Disease

Abstract: We studied the therapeutic efficacy of sulfasalazine and its metabolites sulfapyridine and 5-aminosalicylic acid in nine patients with Crohn's disease and in 23 patients with ulcerative colitis. In a randomized, controlled trial, we treated 11 patients for six weeks with 1 g of sulfasalazine three times a day, seven patients with 0.5 g of sulfapyridine three times a day, and 14 patients with 0.5 g of 5-aminosalicylic acid suppositories three times a day. The clinical state of the disease was characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1
10

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(81 citation statements)
references
References 25 publications
0
70
1
10
Order By: Relevance
“…They do this by reducing synthesis of inflammatory cytokines and have been used for many years. 61 They are medications that can cause a host of side effects from common ones including nausea, vomiting and GI upset. 62 However, three are of particular importance and interest to dentists.…”
Section: -Asasmentioning
confidence: 99%
“…They do this by reducing synthesis of inflammatory cytokines and have been used for many years. 61 They are medications that can cause a host of side effects from common ones including nausea, vomiting and GI upset. 62 However, three are of particular importance and interest to dentists.…”
Section: -Asasmentioning
confidence: 99%
“…Pharmacokinetic studies have demonstrated that su lphasalaz ine passes through the upper gastrointestinal trace unmodified until it reaches the colon, where it is metabolized by e ndogenous bacteria to yield 5-aminosalicylic ac id (5-ASA) and sulfapyridine. Several clinical studies have demonstrated that 5-ASA is the pharmacologically active moiety of sulphasalazine (2)(3)(4) .…”
Section: U Lcerative Colitis Is a Recur-mentioning
confidence: 99%
“…In practice, it is a reasonable rule of thumb to start oral steroids if diarrhoea fails to improve within 3 days of starting rectal steroids given as an enema or foam. A trial comparing the effects of oral prednisone in dosages of 20 mg, 40 mg and 60 mg per day showed that 40mg was more effective than 20mg but that there was no advantage in increasing the dosage further to 60 mg per day which caused more side-effects (14). Prednisolone, 40 mg given in one daily dose, is as effective as 10 mg four times per day (15) and is likely to cause less adrenal suppression (16).…”
Section: J M Rhodesmentioning
confidence: 99%
“…Sixty per cent of these patients with severe colitis will then go into remission if treated with an intensive regimen of intravenous feeding, intravenous prednisolone-2 1-phosphate, 60 mg per day, and intravenous tetracycline, 250 mg four times per day (19,20). Not all components of this regimen have been assessed separately.…”
Section: J M Rhodesmentioning
confidence: 99%
See 1 more Smart Citation